The right kind of fool - Thomas, Sarah Loudin (Bethany House, a division of Baker Publishing Group, 2020)
"Thirteen-year-old Loyal Raines is supposed to stay close to home on a hot summer day in 1934. When he slips away for a quick swim in the river and finds a dead body, the ripples caused by his discovery will impact the town in ways no one could have imagined"--